APPLICATION OF FINANCING BASED WARRANTY CONTRACT OF PRINCIPLES FOR SETTLEMENT WITH RESPECT TO THE RESULTS AND FINANCING PROBLEMS - Zulfi Diane Zaini; Arifin Arifin; Lukmanul Hakim; Aprinisa Aprinisa (Tadulako Law Review, 2018)
A collateral is prohibited in contract based on profit sharing, because this contract is trust-based agreements. But in order to avoid high credit/financing risk, shariah banking in practice implements it. In addition, the binding of collateral used ini shariah banking still uses conventional agreements. This research uses normative law approach(literature research). The result if this research is a collateral has an importen position in the contract based on profit sharing in shariah bank is accordance with the prudential banking principle and sharia compliance because a collateral is applied not as assurance effort of the financial capital, but to guarantee the orderly repayment/settlement of amount of the obligations and profit sharing ratio at the time in accordance with the agreed upon agreement and the disbursement after the customer’s proven negligence, the binding of collateral using the conventional binding provided in the exixting positive law, it has not specialy accommodated the shariah principle and collateral has an urgent function as part of the settlement of financing problems and executed after the customer is declared negligent